Festival as Cultural Diplomacy: KurultÃ¡j and Its Implementation in Hungary - Pratama, Cakra Diaz; Utomo, Ario Bimo (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Diplomatic endeavours encompass a range of strategies, including the organisation of cultural festivals, which serve not only as a means of engaging a broader audience but also as platforms for expressing a nation's identity. One notable example is the KurultÃ¡j festival, which took place in Hungary under the auspices of the Magyar TurÃ¡n AlapÃtvÃ¡ny. This festival exemplifies the practice of cultural diplomacy, attracting participation from various Central Asian nations. Through cultural diplomacy, participating countries aim to promote their respective national interests within the framework of the KurultÃ¡j festival. This article examines the implementation of the KurultÃ¡j festival between 2008 and 2022, focusing specifically on its association with neo-propagandist cultural diplomacy. It argues that the KurultÃ¡j festival cannot be solely categorised as a manifestation of neo-propagandist cultural diplomacy.